Effect of a preventive intervention programme on the prevalence of anterior knee pain in volleyball players - Cumps, E.; Verhagen, E. A.; Duerinck, S.; Deville, A.; Duchene, L.; Meeusen, R. (European Journal of Sport Science, 2008)
Chronic knee disorders, such as patellofemoral pain syndrome and patellar tendinosis, are common injuries in volleyball players. Using a randomized clinical trial, the aim of the present study was to determine the effect of a 4-month in-season intervention programme on the prevalence of anterior knee pain in volleyball players. No significant differences were observed between the intervention and control group for the prevalence of anterior knee pain after the intervention programme (odds ratio =1.58 [95% confidence interval: 0.60-4.20]). Also, no significant differences were observed for individuals with previously sustained anterior knee pain (OR =0.81 [95% CI: 0.33-2.20]). It was revealed that the risk for recurrent anterior knee pain is significantly higher than the risk for newly sustained anterior knee pain (OR =5.79 [95% CI: 1.59-21.00]). In conclusion, we were unable to confirm any preventive effect of the intervention programme on the prevalence of anterior knee pain. However, a previous study using the same intervention and measuring the effect on the intrinsic risk factors of anterior knee pain showed a positive effect.